Foto-reportaje de la comida típica de Llano Chico - Bonilla Narváez, Stefany Alexandra (2017)
Food is a fundamental part of the human body, through the elaboration of typical dishes in the parish of Llano Chico has been contributing to the society, rescuing the cultural traditions, ancestral maintaining a culinary identity of the indigenous Ecuadorians. The society aims to achieve challenges in gastronomy, reducing unhealthy food, so it is very important in the community of Llano Chico emphasize these dishes with creativity because they are the heritage of the community. The different forms of preparation impel family bonding, such recipes come from previous generations. Taking into account it, through photo-reporting will be able to visualize photographic images of the typical dishes of Llano Chico, fiestas and traditions to achieve the recovery of typical food based on the actual information that has been obtained. Through the camera can be captured the historical memory of the moment that is being made, the essence of photography is the original representation and the conception of how each one looks at reality and how he wants to represent it. This research product tries to demonstrate the typical food of Llano Chico, through photos of the delicious dishes that society consumes, interviews with residents and authorities, traditional celebrations offering food in thanks.